Optimizing abstractive summarization with fine-tuned PEGASUS - Rafi, Sadiul Arefin; Rahman, Naimur; Islam, Kazi Nazibul; Ahmad, Ha-mim (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.